2019
DOI: 10.1186/s12987-019-0152-7
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty quantification of parenchymal tracer distribution using random diffusion and convective velocity fields

Abstract: Background Influx and clearance of substances in the brain parenchyma occur by a combination of diffusion and convection, but the relative importance of these mechanisms is unclear. Accurate modeling of tracer distributions in the brain relies on parameters that are partially unknown and with literature values varying by several orders of magnitude. In this work, we rigorously quantified the variability of tracer distribution in the brain resulting from uncertainty in diffusion and convection m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 77 publications
1
57
0
Order By: Relevance
“…However, all these studies were done with modeling that was on the micro-scale over shorter time periods. To the authors' knowledge, the only other study 35 that has considered macroscopic modeling on the time-scales of hours and days, where uncertainties representing both variations in ADC and paravascular velocities where modelled with extensive testing using Monte Carlo methods. They found that, in particular, the CSF tracer distribution within the deep white matter found in 11 could not be explained by diffusion alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, all these studies were done with modeling that was on the micro-scale over shorter time periods. To the authors' knowledge, the only other study 35 that has considered macroscopic modeling on the time-scales of hours and days, where uncertainties representing both variations in ADC and paravascular velocities where modelled with extensive testing using Monte Carlo methods. They found that, in particular, the CSF tracer distribution within the deep white matter found in 11 could not be explained by diffusion alone.…”
Section: Discussionmentioning
confidence: 99%
“…Other osmotic processes might be at play. 145 Non-physiological flow induced by injection of tracer parti-146 cles has been offered as an explanation (24,(30)(31)(32)(33)(34), though 147 Mestre, Tithof et al (6) measured flow speeds that had in-148 significant dependence on whether injection was in progress, 149 and insignificant decay after injection ceased. Those authors 150 also demonstrated that altering the artery wall motion sub-151 stantially changed CSF flow characteristics and significantly 152 reduced the mean flow speed.…”
Section: R a F Tmentioning
confidence: 99%
“…Hadaczek et al (18) proposed that the dilations and constric-28 tions traveling along artery walls with each heart beat might 29 drive CSF in the same direction, in a peristalsis-like mecha-30 nism they dubbed "perivascular pumping." As evidence, they 31 presented experimental results showing that macromolecules 32 injected into the central nervous systems of rats were trans-33 ported further in animals with beating hearts than in ani-34 mals whose hearts had recently been stopped. Iliff et al (19)…”
mentioning
confidence: 99%
“…blood to the brain parenchyma by two main features, including the tight junction (TJ) complex that seals the paracellular space between the endothelial cells, and low level of transcytosis through the endothelium (5)(6)(7)(8). Prior approaches to circumvent the BBB have led to limited success: convection enhanced delivery has limited success in the clinical trials (9), intrathecal delivery has limited parenchymal penetration (10). Methods to increase BBB permeability such as using high osmotic mannitol have significant neurotoxicity (11,12).…”
mentioning
confidence: 99%